Los recursos fitogenéticos del CATIE: bienes estratégicos para la diversificación y mejora de la producción agrícola y forestal de pequeños productores - Ebert, Andreas (2004)
The examples presented for various crops clearly show that the germplasm collections held in trust by CATIE constitute a strategic resource for diversification and improvement of the production of agricultural and forestry commodities by small farmers. With both perennial and annual crops, the Theme Group "Sustainable Management and Use of Plant Genetic Resources" (TG SMU-PGR) promotes rational management and use of this important resource for the benefit of the farmers in the region. Through the selection and validation of materials with resistance to diseases and pests and with potential for mixed production systems, the TG SMUPGR contributes to diversified production with less risk for the farmers and increased benefits for the ecosystem and the environment. Ultimately, this leads to more stable yields, increased food security and agrobiodiversity, as well as diversified agricultural and forestry production systems.